Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Persepsi Harga Terhadap Keputusan Pembelian di Kedai Kopi Janji Jiwa - Indriani, Dini; Prawoto, Prawoto (Indonesian Journal Publisher, 2024)
This study aims to investigate the effect of product quality, service quality, and price perception on purchasing decisions at Janji Jiwa Coffee Shop. A total of 106 respondents, who were customers visiting Kopi Janji Jiwa, were collected using an accidental sampling technique. Primary data was gathered through questionnaires and analyzed using quantitative methods with SPSS20 software. The results revealed that product quality does not significantly influence purchasing decisions. In contrast, service quality and price perception have a significant impact on purchasing decisions. The findings suggest that product quality does not affect purchasing decisions when consumers do not consider product quality as a factor in their purchase decision-making process. Service quality influences purchasing decisions when consumers consider the quality of service provided during the decision-making process. Additionally, price perception affects purchasing decisions when consumers take into account the product price in their decision to purchase or not. The study concludes that enhancing service quality and managing price perception are crucial for influencing consumer purchasing decisions at Janji Jiwa Coffee Shop.